Kickstart manufacturing SMEs' go green journey : A green hydrogen acceptance framework to enhance low carbon emissions through green digital technologies - Muhammad Farhan, Jalil; Dayang Affizzah, Awang Marikan; Mohamad, Jais; Mohammad Affendy, Arip (Elsevier Ltd., 2025)
The manufacturing sector, a major contributor to global carbon emissions, is under growing pressure to adopt sustainable practices. Despite its potential, green hydrogen as a clean energy solution faces significant challenges, including limited technological feasibility, high costs, insufficient regulatory support, inadequate infrastructure, low market demand, and lack of awareness. This study addresses these barriers by proposing a novel framework that integrates green hydrogen acceptance and green digital technologies to kickstart manufacturing SMEs' “Go Green” journey and enhance low carbon emission performance. The research investigates critical factors influencing green hydrogen acceptance—such as technological feasibility, economic viability, regulatory support, infrastructure development, market demand, and awareness—and evaluates the mediating role of green digital technologies in reducing emissions. Data were collected from 343 owners and managers of manufacturing SMEs in Malaysia and analysed using Structural Equation Modelling (SEM) with AMOS 24.0 software. Findings reveal that the proposed framework significantly enhances low carbon emission performance, with green digital technologies playing a partial mediating role. This framework provides practical insights for SMEs to adopt sustainable energy solutions and digital innovations, fostering a supportive ecosystem for sustainability. Its real-world application empowers SMEs to reduce carbon footprints, meet regulatory goals, and gain a competitive edge in the green economy.